School-level perceptions and enforcement of the elimination of nonmedical exemptions to vaccination in California - Taylor A. Holroyd; Amanda C. Howa; Tina M. Proveaux; Paul L. Delamater; Nicola P. Klein; Alison M. Buttenheim; Rupali J. Limaye; Saad B. Omer; Daniel A. Salmon (Human Vaccines & Immunotherapeutics, 2021)
In 2015, California passed Senate Bill 277 eliminating all nonmedical exemptions to school vaccinations. We aimed to explore school-level modes of SB277 enforcement, characterize vaccination knowledge, attitudes, and beliefs of school officials, and identify whether school vaccination policies are associated with medical exemptions being granted. Surveys were mailed to a stratified random sample of 1,450 schools in California. School personnel (n = 752) reported their medical training, vaccination beliefs, enforcement of vaccination policies, and school rates of medical exemptions. Multiple logistic regression was used to assess whether school policies are associated with the likelihood of medical exemption requests being granted. Nurses were more likely than non-nurses to hold beliefs recognizing the importance of vaccination. A school where the survey respondent was a nurse was more likely to have granted a medical exemption request compared to a school where the respondent was not a nurse (OR 2.11, 95% CI 1.34–3.36). The training of school officials and school-level practices may impact the enforcement of medical exemptions. Equipping school officials as competent sources of vaccine information for concerned parents will be valuable in improving parental vaccine uptake.